2018
DOI: 10.1093/gji/ggy171
|View full text |Cite
|
Sign up to set email alerts
|

Marine magnetotelluric inversion with an unstructured tetrahedral mesh

Abstract: The finite element method using an unstructured tetrahedral mesh is one of the most effective methods for the 3-D modelling of marine magnetotelluric data that are strongly affected by bathymetry, because it enables us to incorporate both small-scale and regional-scale bathymetry into a computational mesh with a practical number of elements. The authors applied a 3-D inversion scheme using mesh of this type to marine magnetotelluric problems for the first time and verified its applicability. Forward calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We concluded that the 2-D inversion models obtained in the manner we applied to the observed data represent the main features of a possible 3-D electrical resistivity structure. Further, we carry out a 3-D inversion with the observed MT impedances using a program of Usui (2015) and Usui et al (2018), even though the data set may not be suitable for 3-D inversion because the MT impedances are available only along the transect (Figure 1). Details of the 3-D inversion are described in Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the 2-D inversion models obtained in the manner we applied to the observed data represent the main features of a possible 3-D electrical resistivity structure. Further, we carry out a 3-D inversion with the observed MT impedances using a program of Usui (2015) and Usui et al (2018), even though the data set may not be suitable for 3-D inversion because the MT impedances are available only along the transect (Figure 1). Details of the 3-D inversion are described in Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we carry out a 3‐D inversion with the observed MT impedances using a program of Usui (2015) and Usui et al. (2018), even though the data set may not be suitable for 3‐D inversion because the MT impedances are available only along the transect (Figure 1). Details of the 3‐D inversion are described in Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the field geophysical observations from magnetotelluric (MT) and geomagnetic deep sounding (GDS) have confirmed that there is widespread existence of a large quantity of the anomalously high electrical conductivity phenomena in these typical regions of oceanic crust [1][2][3] and West African craton [4]. As a representative basic intrusive rock, it is well known that gabbro is widely outcropped in these global tectonic units of oceanic crust and craton regions, and its corresponding dominant mineralogical composition is constituted of clinopyroxene and plagioclase [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Finite difference (FD) and finite element (FE) methods are mostly developed and applied as the main process of forward calculation for 2-D and 3-D inversions (Egbert and Kelbert 2012;Franke et al 2007;Key and Weiss 2006;Kordy et al 2016a, b;Lee et al 2009;Mackie et al 1993;Nam et al 2007;Ren et al 2013;Sarakorn 2017;Sharma and Kaikkonen 1998;Siripunvaraporn et al 2002;Usui 2015;Usui et al 2017Usui et al , 2018Wannamaker et al 1986Wannamaker et al , 1987. The FD method is accurate for simple modeling and, because of the limitation of the structured rectangular mesh, consumes less memory storage and computation time.…”
Section: Introductionmentioning
confidence: 99%
“…The FD method is accurate for simple modeling and, because of the limitation of the structured rectangular mesh, consumes less memory storage and computation time. The FE method is accurate for real-world complex modeling, especially topography and bathymetry, because of the greater flexibility of mesh schemes (Franke et al 2007;Grayver and Kolev 2015;Grayver 2015;Key and Weiss 2006;Kordy et al 2016a, b;Lee et al 2009;Nam et al 2007;Ren et al 2013;Sarakorn 2017;Sharma and Kaikkonen 1998;Usui 2015;Usui et al 2017Usui et al , 2018Wannamaker et al 1986Wannamaker et al , 1987. However, the disadvantages of FE are greater consumption of memory storage and longer computation time.…”
Section: Introductionmentioning
confidence: 99%